A newly developed kelulut honey drink enriched with seaweed by using design of experiment approach - Wong, Pearly; Hii, Siew-Ling; Lim, Shok-Ni; Koh, Chen-Chung; Suzy Rini Ak Gindi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
A novel functional drink, Kelulut honey enriched with seaweed (designated as KhS), was successfully developed by using design of experiment (DOE) approach in this study. A two-level-factor Full Factorial Design (FFD), 22, was employed to screen the interactions among the two major composition (Kelulut honey and seaweed) as well as to analyse the effect of these ingredients towards the sensory and proximate properties of the newly developed product. The design of experiment (DOE) and data analysis were executed by using Design- Expert Software. Two main approaches of hedonic tests, i.e., the measurement of preference and the measurement of acceptance were applied during sensory evaluation. Results indicated that amount of seaweed and honey used during the preparation of KhS did affect the moisture content and pH of the end product significantly. Sensory evaluation revealed that the overall acceptability score of the newly developed Kelulut honey enriched with seaweed drink was prefered moderately by most of the panelists and thus it could be a favourable product to be commercialised in the market.